Clinical Efficacy of Vertical or Parallel Technique of a Micro‐Locking Plate for Treatment of Dubberley B‐Type Capitellar Fractures. Issue 1 (10th January 2021) - Lu, Yao; Fu, Lei; Ma, Teng; Xu, Yi‐bo; Xu, Li‐ping; Song, Zhe; Fan, Shan; Wang, Qian; Sun, Liang; Xue, Han‐zhong; Li, Zhong; Zhang, Kun; et al.
Abstract : Objective: To evaluate the clinical efficacy of micro‐locking plate through vertical or parallel technique for treatment of Dubberley B‐type capitellar fractures. Methods: A retrospective analysis was performed in 24 patients (17 males and seven females, with an average age of 44.9 years, range from 19 to 75 years) with capitellar fractures that were treated with micro‐locking plate using vertical or parallel technique between January 2016 to January 2019. The inclusion criteria include closed capitellar fracture, normal anterior elbow joint movement before injury, and recent capitellar fracture with injury within past 3 weeks. Fractures classified according to Dubberley included four cases of type IB, eight cases of type IIB, and 12 cases of type IIIB. Radiographic evaluation was performed. Surgery time, blood loss, range of motion of the elbow, forearm rotation, and complications were recorded. Elbow joint function was evaluated by Mayo Elbow Performance Score (MEPS). Results: The mean follow‐up period was 19.6 months (range, 12–36 months). The average clinical healing time for fractures was 11.2 ± 3.2 weeks (range, 8–20 weeks). Fracture united in all patients. Two patients showed slight delayed union, but union was achieved eventually. The mean time from injury to surgery was 6.3 ± 3.1 days (range, 2–15 days). The average surgical time was 68.1 ± 11.5 min (range, 50–90 min), and the mean blood loss was 75.2 ± 26.5 mL (range, 40–120 mL). The mean range of flexion was 122.5° ± 10.5°(range, 95°–140°). The mean range of extension was 8.5° ± 5.8°(range, 0°–20°). The mean range of pronation was 79.7° ± 8.0°(range, 65°–90°). The mean range of supination was 80.5° ± 7.1°(range, 60°–90°). The mean MEPS at final follow‐up was 89.8 ± 9.0 (range, 60–100). Based on the MEPS, 18 (75%) patients had excellent, five (20.8%) patients had good, and one (4.2%) patient had fair. None of the 24 patients suffered vascular or nerve injury. One patient showed superficial infection, which was treated with surgical dressing. Conclusions: The vertical or parallel technique of the micro‐locking plate is an excellent method for treating Dubberley B‐type capitellar fractures. Abstract : The micro‐locking plate accroding to vertical or parallel technique is an excellent method for Dubberley B‐type capitellar fractures.